BLIND SPOTS OF INFORMATION OPERATIONS: OF MICRO PROPAGANDA, ALGORITHM GAMING & HOW TO PROFIT FROM IT - Neudert, Lisa-Maria; Bradshaw, Samantha; Lewis, Rebecca; Yin, Leon; Woolley, Samuel; Joseff, Katie; Metaxa, Danaë; Hogan, Alexander (AoIR Selected Papers of Internet Research, 2019)
Techniques designed to manipulate public opinion and undermine information ecosystems are rapidly evolving while research lags behind technological innovation and strategic expertise. As a more sophisticated generation of information operations is fast to mature, the papers in this panel shed light on some of the blind spots of scholarly inquiry making visible new thematic strategies, technical infrastructures and both political and economic incentives. The first two papers examine the progression from general political propaganda geared towards influencing elections to highly issue-specific micro-propaganda. The first paper presents an analysis of anti-Semitic disinformation campaigns and harassment during the 2018 US midterms on Twitter and offers rich evidence from interviews with Jewish American opinion leaders about their impact. Drawing on data from Twitter’s Election Integrity Initiative, the second paper examines the gender dimensions of foreign influence operations and how hostile state actors frame and discuss gender identity & politics. The third paper presents an analysis of search engine optimization strategies that extremist YouTubers use in an attempt to game the algorithm and increase their visibility in the network. The fourth paper investigates the relationship between partisan bias associated with Google Search results and the success of political candidates associated with the search queries during elections and finds that partisan search media is a predictor for election outcomes. The fifth paper examines the emergence of a global political economy for manipulation and offers a grounded typology of the vendors, marketplaces, services, and products that are designed to turn a profit from swaying public opinion.